Desenvolvimento e implementação de uma metodologia de chaveamento para reguladores estáticos de baixa tensão - Lima, Rodrigo Nobis da Costa (2022)
Among the several phenomena related to power quality issues, long and short-term voltage variations represent the most common phenomena in electrical systems in general. In this context, in particular, voltage dips and swells represent the most harmful disturbances to electric power utility customers, leading to stoppages in production processes in a large number of commercial and industrial facilities. Fortunately, there are currently some technical solutions commercially available to mitigate the effects of these voltage events. One of these solutions is the use of static voltage regulators, which are basically composed of magnetic devices (transformers or autotransformers) that perform voltage control through static switching of taps in their primary or secondary coils. The subject has been explored by the scientific community since the early 1990s. However, several of the proposed methodologies have limitations that are difficult to overcome in some situations, such as, for example, the need for knowledge of the instantaneous current zero crossing to perform the switching of static switches, as well as the lack of technical detail necessary for the replication of some of these methodologies and the exorbitant costs of implementation, making its use unfeasible for most practical applications. In this sense, the present work has the goal of presenting a proposal for the design of a new static voltage regulator capable of performing tap changes faster than those presented in the available literature. This new concept of static voltage regulator also includes an easy implementation, with few input variables and, mainly, without the need to measure the instantaneous current signal to identify zero crossing. To present the proposed methodology, resulting in a new concept of static voltage regulator, mathematical models were implemented based on computer simulations, aiming the analysis of the performance of the main aspects of the proposed methodology. Finally, the presented switching methodology was implemented in a small-scale laboratory prototype. The results demonstrated the technical feasibility of the proposed method, as well as the possibility of its application in real networks in a very promising way.